2001
DOI: 10.1021/cm000858n
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Transparent Particulate MoO3/TiO2 and WO3/TiO2 Films and Their Photocatalytic Properties

Abstract: By monolayer coverage of highly acidic semiconductors, such as MoO 3 and WO 3 on the surface of TiO 2 nanoparticles (Degussa P25), the stability of colloidal suspensions in aqueous solution can be greatly improved. The average diameter of agglomerated MoO 3 /TiO 2 and WO 3 /TiO 2 particles in aqueous suspension is only 85-110 nm, respectively, which is about one-fifth to one-fourth of that of pure TiO 2 suspension. The optically transparent photocatalytic films have been prepared with deposition of these collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(100 citation statements)
references
References 22 publications
3
96
0
1
Order By: Relevance
“…There has been much interest in coupling different semiconductor particles with TiO 2 , with coupled samples such as TiO 2 -CdS, Bi 2 S 3 -TiO 2 , TiO 2 -WO 3 , TiO 2 -SnO 2, TiO 2 -MoO 3, and TiO 2 -Fe 2 O 3 being reported [111][112][113][114][115][116][117][118]. The coupled structure that has received the most attention is that consisting of CdS and TiO 2 colloidal particles.…”
Section: Coupled/composite Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much interest in coupling different semiconductor particles with TiO 2 , with coupled samples such as TiO 2 -CdS, Bi 2 S 3 -TiO 2 , TiO 2 -WO 3 , TiO 2 -SnO 2, TiO 2 -MoO 3, and TiO 2 -Fe 2 O 3 being reported [111][112][113][114][115][116][117][118]. The coupled structure that has received the most attention is that consisting of CdS and TiO 2 colloidal particles.…”
Section: Coupled/composite Tiomentioning
confidence: 99%
“…WO 3 can be excited by illumination with visible light and the photogenerated holes can transfer from WO 3 to TiO 2 . Song et al [115] observed that loading of WO 3 on the TiO 2 surface improved the decomposition of 1,4-dichlorobenzene in aqueous solution by up to 5.9 times compared with pure TiO 2 . Because the standard reduction potential between W(VI) and W(V) is only -0.03 V, it was deduced that electrons in the conduction band of TiO 2 could be easily accepted by WO 3 .…”
Section: Coupled/composite Tiomentioning
confidence: 99%
“…Further, the strong oxidizing power of the photogenerated holes, the chemical inertness, and the non-toxicity of TiO 2 has also made it a superior photocatalyst [4]. Titania has a large band gap (3.20 ev for anatase TiO 2 ) and therefore, only a small fraction of solar light can be absorbed [5]. Many attempts have been made to sensitize titanium dioxide to the whole visible region, such as doping with transition metals [6][7], transition metal ions [8], nonmetal atoms [9] and organic materials [10].…”
Section: Introductionmentioning
confidence: 99%
“…Electron injection into the bulk WO 3 layer was invoked as a mechanism for reduced surface carrier recombination in the TiO 2 component in these composites [17]. The photocatalytic activity of WO 3 -TiO 2 films was found to be three times higher than that of pure TiO 2 films for the gas-phase oxidation of 2-propanol [18]. A TiO 2 coating was coupled with a WO 3 ''electron pool'' in the design of a photoelectrochemical anticorrosion system with built-in energy storage capability [19].…”
Section: Introductionmentioning
confidence: 99%